Police Decision-Making in the Absence of Evidence-Based Guidelines: Assessment of Alcohol-Intoxicated Eyewitnesses - Pettersson, Daniel; Bergquist, Magnus; Hagsand, Angelica V. (Frontiers in Psychology, 2022)
Regarding police procedures with alcohol-intoxicated witnesses, Swedish police officers have previously reported inconsistent and subjective decisions when interviewing these potentially vulnerable witnesses. Most officers have also highlighted the need for national policy guidelines aiding in conducting investigative interviews with intoxicated witnesses. The aims of the two studies presented here were to investigate whether; (1) police officers’ inconsistent interview decisions are attributable to a lack of research-based knowledge; (2) their decision to interview, as well as their perceptions of the witnesses’ credibility could be influenced by scientific research; (3) police officers decision-making and perceptions of witness credibility is biased by pre-existing social norms. In two separate randomized online experiments, police professionals and recruits (Study 1, N = 43; Study 2, N = 214) watched a recorded fictive witness interview, to which they were asked to rate the probability of interviewing the witness, the witness’ credibility, and to estimate the witness’ level of intoxication. Results showed that interview probability and perceived witness credibility was affected by witness intoxication level. While it cannot be stated definitely from the present research, these findings provided indications that police officers and recruits lacked research-based knowledge. Results also showed that interview probability, but not perceptions of credibility, was influenced by a research-based message. In line with research, interview probability for the most intoxicated witness increased after reading the message. Unexpectedly, neither interview probability nor witness credibility was affected by social norms. The current findings added to the legal psychology literature by showing that a breath alcohol concentration (BrAC) as low as 0.04% was enough for police officers and recruits to consider intoxicated witnesses less credible than sober witnesses. Findings also indicated that, despite the lower credibility assessment, police may have some understanding that these witnesses can be interviewed at low intoxication levels (i.e., around 0.04%). However, this willingness to interview intoxicated witnesses ceased at a BrAC lower than the levels where research has found intoxicated witnesses as reliable as sober witnesses (i.e., BrAC < 0.10%). Future directions for research and policy development as well as theoretical and practical implications of the present findings are discussed.